Alignment of paired molecules of C60 within a hexagonal platform networked through hydrogen-bonds. Issue 63 (15th July 2016) - Hisaki, Ichiro; Nakagawa, Shoichi; Sato, Hiroyasu; Tohnai, Norimitsu
Abstract : A hydrogen-bonded low-density organic framework achieved periodic alignment of paired molecules of C60 . Abstract : We demonstrate, for the first time, that a hydrogen-bonded low-density organic framework can be applied as a platform to achieve periodic alignment of paired molecules of C60, which is the smallest example of a finite-numbered cluster of C60 . The framework is a layered assembly of a hydrogen-bonded 2D hexagonal network (LA-H-HexNet) composed of dodecadehydrotribenzo[18]annulene derivatives.